2014
DOI: 10.1111/bph.12835
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bias in CCR1 antagonists using radiolabelled binding, receptor internalization, β‐arrestin translocation and chemotaxis assays

Abstract: BACKGROUND AND PURPOSEInvestigators have suggested that the chemokine receptor CCR1 plays a role in multiple myeloma. Studies using antisense and neutralizing antibodies to CCR1 showed that down-regulation of the receptor altered disease progression in a mouse model. More recently, experiments utilizing scid mice injected with human myeloma cells demonstrated that the CCR1 antagonist BX471 reduced osteolytic lesions, while the CCR1 antagonist MLN-3897 prevented myeloma cell adhesion to osteoclasts. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We found that a small molecule-biased antagonist acted similarly to a peptide-biased antagonist to avoid tolerance, which suggests that flexibility in the design of such agents is possible. Currently, very few biased antagonists have been characterized, and the advantages of biased antagonists in general remain an unexplored avenue for drug discovery (24)(25)(26)(27). Our study suggests that biased antagonists can potentially provide therapeutic options to patients who develop tolerance to unbiased antagonists.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We found that a small molecule-biased antagonist acted similarly to a peptide-biased antagonist to avoid tolerance, which suggests that flexibility in the design of such agents is possible. Currently, very few biased antagonists have been characterized, and the advantages of biased antagonists in general remain an unexplored avenue for drug discovery (24)(25)(26)(27). Our study suggests that biased antagonists can potentially provide therapeutic options to patients who develop tolerance to unbiased antagonists.…”
Section: Discussionmentioning
confidence: 79%
“…This binding site cannot be predicted on the basis of the amino acid sequence of the peptide corresponding to TM2 and ECL1 of CXCR4. The current model for the interaction of CXCL12 with CXCR4 suggests that Lys 25 in the N terminus of the receptor binds to the N-loop region of the chemokine (30). The amino acid sequence of X4-2-6 does not have lysine residues (33).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ligand-receptor analysis showed that the CCL6-CCR1 and CCL9-CCR1 pairs made the most significant relative contributions (Figure 5D). Ccr1 is mainly expressed in monocytes, T cells, dendritic cells, and neutrophils, whereas Ccr2 is mainly expressed in macrophages in the immune system (19,20). Previous research has demonstrated that Ccr2, instead of Ccr1, is the sole receptor responsible for monocyte mobilization from the bone marrow and recruitment to inflamed sites (21).…”
Section: Cellchat and Single-cell Trajectories Reveal Cell Communicat...mentioning
confidence: 99%
“…As such, it is conceivable that a small-molecule antagonist with similar properties could be developed to target CCR4 and block CCL17signaling while sparing CCL22 signaling and therefore T reg recruitment. CCR1-specific small molecules have already been described that inhibit chemotactic responses to CCL3, but have no effect on b-arrestin recruitment (22). Peptide-based chemokine receptor agonists and antagonists have been described in the literature-several of which target CXCR4 including the 17mer CXCR4 agonists RSVM and ASLW (64), peptide fragments that were derived from the CXCL12 sequence and ALX40-4C, a CXCR4 antagonist polypeptide of 9 Arg residues stabilized by terminal protection and inclusion of D-amino acids (65).…”
Section: Mechanistic Explanations For Biased Agonism At Ccr4mentioning
confidence: 99%